Research progress of interleukin-15 in cancer immunotherapy - Cai, Menghan; Huang, Xuan; Huang, Xiting; Ju, Dianwen; Zhu, Yi Zhun; Ye, Li (Frontiers in Pharmacology, 2023)
Interleukin-15 (IL-15) is a cytokine that belongs to the interleukin-2 (IL-2) family and is essential for the development, proliferation, and activation of immune cells, including natural killer (NK) cells, T cells and B cells. Recent studies have revealed that IL-15 also plays a critical role in cancer immunotherapy. IL-15 agonist molecules have shown that IL-15 agonists are effective in inhibiting tumor growth and preventing metastasis, and some are undergoing clinical trials. In this review, we will summarize the recent progress in IL-15 research over the past five years, highlighting its potential applications in cancer immunotherapy and the progress of IL-15 agonist development.